Influence of ASE Noise on the Performance of DWDM Networks Using Low-Power Pumped Raman Amplifiers. Issue 2 (3rd March 2016) - Bui, Trung Ninh; Nguyen, Quoc Tuan; Pham, Van Hoi
ABSTRACT: We present the results of investigation of influence of amplified spontaneous emission (ASE) noise, noise figure (NF) and dispersion chromatic on the performance of middle-distance dense-wavelength-division-multiplexing (DWDM) networks using low-power pumped distributed Raman amplifiers (DRAs) in two different pump configurations, i.e., forward and backward pumping. We found that the pumping configurations, ASE noise, and dispersion play an important role for improving the network performance by reduction of NF and bit error rate (BER) of the system. Simulation results show that the lowest BER and low NF were obtained, when using the forward pumping configuration. Moreover, we have also compared ASE noise powers of the simulation with this experiment. These results conclude that DRA with low pump power (<1 W) is the promising key technology for short- and/or middle-distance DWDM transmission networks.